Clinical self-tracking and monitoring technologies: negotiations in the ICT-mediated patient–provider relationship. Issue 1 (2nd January 2017) - Piras, Enrico Maria; Miele, Francesco
ABSTRACT: This paper discusses mediation in the patient–provider relationship arising from the introduction of digital technology for a specific form of monitoring: 'clinical self-tracking'. Focusing on the management of type 1 diabetes, a condition that requires significant self-management by patients, we describe how the actors negotiated a new ICT-mediated relationship in three hospital departments. The analysis followed a qualitative design and was carried out by interviewing patients, clinicians and technology developers and by analysing messages exchanged through the ICT tool. We first show how each department customised the system by drawing on already existing care practices, organisational goals and representations of the department's desired relationship with the patients. We then focus on patient–provider relationships, showing that, while the clinical self-tracking sometimes followed the path desired by the providers, at other times, it developed in unexpected ways. We distinguish among three emerging categories of self-tracking: self-tracking for remote management, self-tracking for e-learning and self-tracking as boundary setting. The analysis reveals how the new patient–provider relationship arises from an open-ended process. Providers can push self-tracking practices but cannot steer them; and patients, through an unexpected use of the self-tracking technologies, are able to negotiate a desired relationship with providers.